Association Between Lifestyle and Breast Fibroadenoma - Astri, Nita; Khanifah, Milatun (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2025)
Fibroadenoma is a benign tumor in which epithelial cells are arranged in fibrosa. Although breast fibroadenoma tumors are benign, they can still trigger the risk of developing breast cancer. The purpose of this study is to see if there is a relationship between lifestyle and the incidence of breast fibroadenoma. This Study is a quantitative research using a case-control design. The population in this study consists of all patients examined at the surgical polyclinic of kratos hospital from December 2023 to January 2024 with a population of 114. The chi square hypothesis test with a p-value of 0.000 means that < 0.05 statistically there is a significant relationship between lifestyle and the incidence of breast fibroadenoma. Lifestyle changes and hereditary factors are triggers for the onset of breast diseases, including fibroadenoma and cancer. The relationship between lifestyle and breast fibroadenoma shows that there is a statistically significant relationship between lifestyle and breast fibroadenoma. Patients with poor lifestyles were 9,679 times more likely to develop breast fibroadenoma compared to patients with good lifestyles.Keywords: Life Style, Breast Fibroadenoma